ANALYSIS OF THE SERVICES MARKETING MIX OF GOFOOD IN PEKANBARU CITY USING IMPORTANCE PERFORMANCE ANALYSIS METHOD - Taufik Setiawan; Fajar Restuhadi; Deby Kurnia (Fakultas Pertanian, Universitas Riau, 2021)
The marketing mix is important for companies in running their business, including for gofood services. Consumers have expectations of the performance that will be obtained from the company's services. This study aims to analyze the characteristics of gofood consumers in Pekanbaru City and identify aspects of the service marketing mix with the best performance. This research is a survey research with descriptive analysis and Importance Performance Analysis. The results showed that most of the gofood consumers in Pekanbaru City were groups of people who often shopped impulsively, were at an age with a high level of innovation adoption, spread across every sub-district, did not have many dependents, often used social media, had high school education, and low income/still the responsibility of parents. Furthermore, the place aspect becomes the most dominant aspect in the marketing mix.